Pengembangan Bahan Ajar Digital Berbasis Flipbook Pada Mata Kuliah Pembelajaran Sosial Emosional - Rahmi, Rahmi; Sucipto, Sigit Dwi; Dewi, Ratna Sari; Puriani, Risma Anita; Tanjung, Romi Fajar (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
Flipbook-based digital teaching materials for social-emotional learning courses for pre-service PPG students at FKIP UNSRI are still rare. This research aims to produce flipbook-based digital teaching materials for social-emotional learning courses for pre-service PPG students at FKIP Unsri. The development model used is the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. The analysis was carried out involving 11 PPG Pre-service students as research samples. The results of the teaching materials show that the resulting teaching materials have been validated with a media validation percentage value of 91.6% in the very good category, material validation of 95% in the very good category, and language validation of 91.6% in the very good category. The textbook assessment results for each indicator were 89.09 in the very good category. In this way, flipbook-based digital teaching materials for social-emotional learning courses for pre-service PPG students at FKIP Unsri have been successfully developed.